2016
DOI: 10.1074/jbc.m116.744722
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Selection of β-Site APP-Cleaving Enzyme 1 (BACE1) Cleavage Sites in Amyloid β-Protein Precursor (APP) Harboring Protective and Pathogenic Mutations within the Aβ Sequence

Abstract: Edited by F. Anne Stephenson␤␤-Site APP-cleaving enzyme 1 (BACE1), 3 a type I transmembrane aspartic protease, was identified as the ␤-secretase that cleaves amyloid ␤-protein precursor (APP) to generate neurotoxic amyloid ␤ (A␤) (1-4). BACE1 cleaves APP at the peptide bond between Met 671 and Asp 672 (␤-site; sequence numbering refers to the APP770 isoform) (5, 6). This primary cleavage of APP generates the secreted form of the amino-terminal large fragment (sAPP␤) and the membrane-associated carboxyl-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 55 publications
2
49
0
Order By: Relevance
“…sAPP␣ in the conditioned medium is recognized by the W0-2 antibody, whereas sAPP␤ is not detected by antibody W0-2 as it lacks the epitope. However, an alternative minor BACE1 cleavage site of APP, the ␤Ј-site at residue 10 within the A␤ domain (45), would result in the release of the product sAPP␤Ј and would be recognized by the W0-2 antibody. We demonstrated that most if not all the secreted 98-kDa ectodomain of APP in the culture medium represents sAPP␣, as the BACE1 inhibitor C3 did not affect the level of sAPP; moreover, the ␣-secretase inhibitor, TAPI, reduced the levels of sAPP by 78 -85%.…”
Section: Discussionmentioning
confidence: 99%
“…sAPP␣ in the conditioned medium is recognized by the W0-2 antibody, whereas sAPP␤ is not detected by antibody W0-2 as it lacks the epitope. However, an alternative minor BACE1 cleavage site of APP, the ␤Ј-site at residue 10 within the A␤ domain (45), would result in the release of the product sAPP␤Ј and would be recognized by the W0-2 antibody. We demonstrated that most if not all the secreted 98-kDa ectodomain of APP in the culture medium represents sAPP␣, as the BACE1 inhibitor C3 did not affect the level of sAPP; moreover, the ␣-secretase inhibitor, TAPI, reduced the levels of sAPP by 78 -85%.…”
Section: Discussionmentioning
confidence: 99%
“…CLA decrease Ab generation, we first assessed the level of b-site APP-cleaving enzyme (BACE1), which is the enzyme primarily responsible for amyloidogenic cleavage of APP (Vassar et al, 1999;Kimura et al, 2016). Because CLA alters expression of BACE1 but not ADAM10/asecretase in SH-SY5Y cells (Li et al, 2011), we examined protein expression of APP, BACE1, and presenilin 1 amino terminal fragment (PS1 NTF), a catabolic component of active g-secretase complex, in neurons treated with CLA and LA.…”
Section: C9t11 Cla Decreases Bace1 Activity In Neuronal Lysate But mentioning
confidence: 99%
“…The remaining membrane-associated N-terminal region is subject to further processing by the carboxypeptidase-like activity of the gsecretase complex to generate various types of Ab with different carboxyl-terminal gcleaved sites, including the strongly neurotoxic and aggregation-prone Ab42 (Qi-Takahara et al, 2005;Takami & Funamoto 2012). Mutations of AD causative genes, including PSENs and APP, alter Ab generation (Mullan et al, 1992;Goate et al, 1991;Forman et al, 1997), and a protective Icelandic mutation of APP decreases b-cleavage and facilitates b'-cleavage of APP, thereby decreasing production of neurotoxic Ab1-40 and Ab1-42 (Jonsson et al, 2012;Kimura et al, 2016). Accordingly, Ab generation is considered to be a primary cause of AD.…”
Section: Introductionmentioning
confidence: 99%
“…BACE1 is abundant in brain, and in neurons in particular (63,64), and is the primary β-secretase responsible for Aβ production (65) as shown in numerous mouse knock out studies (66)(67)(68)(69) However, the effect on Aβ production is only 28% in heterozygous carriers (73). This mutation also affects the aggregation properties of Aβ (74,75) and induces alternative Bace1 cleavage at the β' site in APP, which might be protective (76). Thus although widely cited as genetic evidence supporting the notion that reducing β-secretase cleavage would benefit patients, the argument remains clearly circumstantial.…”
Section: Fad-linked Mutations Place Long Aβ Central To Diseasementioning
confidence: 99%